The effect of covid-19 fear on healthy lifestyle behaviors in menoposal women: case of southeastern anatolia - CAN GÜRKAN, ÖZLEM (My University, 2022)
Background. The study was conducted to evaluate the effect of Covid-19 fear on healthy lifestyle behaviors in menopausal women living in the Southeastern Anatolia region.Material and methods. As of April and June 2021, a descriptive, cross-sectional and relationship-seeking design study was completed with 203 participants who were in the menopausal period and who were between the ages of 40 and 65 and were living in the provinces of Gaziantep, Diyarbakir, ,Sanliurfa, Batman, Adiyaman, Siirt, Mardin, Kilis,,Sirnak in the Southeastern Anatolia region of Turkey. The data were collected using the descriptive information form prepared by the researchers, the Fear of Covid-19 Scale, the Menopause Symptoms Evaluation Scale and the Healthy Lifestyle Behaviors Scale-II. Descriptive statistical analyses, Mann Whitney U test, Kruskall Wallis H test and Spearman Correlation Analysis were used to analyze the data.Results. The mean age of the participants was 55.7 +/- 5.6 years (min: 40, max: 69), the highest scores in the Healthy Lifestyle Behaviors Scale-II were found in the sub-dimensions of \"spiritual development\" (23.4 +/- 3.2) and \"interpersonal relations\" (23.1 +/- 3.3). In the Menopause Symptoms Evaluation Scale total and sub-dimension scores, it was determined that the \"somatic complaints\" (10.4 +/- 2.6) and \"psychological complaints\" sub -dimensions (10.7 +/- 3.1) had the highest scores.Conclusions. A statistically significant positive correlation was found between the participants\" Fear of Covid-19 Scale scores and Menopause Symptoms Evaluation Scale total and sub-dimension scores. There was a statistically significant positive correlation between the Menopause Symptoms Evaluation Scale and the Healthy Lifestyle Behaviors Scale-II and certain sub-dimensions.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Klinik Tıp; Klinik Tıp (MED); HEALTH CARE SCIENCES & SERVICES; CLINICAL MEDICINE; Clinical Medicine (MED); Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Gözden Geçirme ve Sınav Hazırlığı; Liderlik ve Yönetim; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Sağlık Politikaları; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); Review and Exam Preparation; Leadership and Management; Community and Home Care; Care Planning; Health Policy; healthy lifestyle; menopause; Covid-19; fear